Examining the Antecedents of Entrepreneurial Learning from Failure: A Study of Developing Country Context - Asif, Iqbal; Dr. Mahani, Mohammad Abdu Shakur; Dr. Sharizal, Hashim (Human Resource Management Academic Research Society, 2024)
Entrepreneurship is a challenging and dynamic process that involves risks and uncertainties. Failure is an inherent part of the entrepreneurial journey and can have a profound impact on the learning process and future intentions of entrepreneurs. However, failure can be an essential source of learning and advancement with good coping mechanisms. Entrepreneurs work to accept and attempt to convert failure into an opportunity to learn more, that is, their attitudes and skills, into a more advanced state and knowledge. The study employed a quantitative cross-sectional research design. The data was collected using a structured questionnaire administered to a sample of 318 failed entrepreneurs in the three major cities of Pakistan. The hypothesized model was tested using partial least squares structural equation modeling (PLS-SEM) technique. The results indicate that five factors are essential antecedent relationships for entrepreneurial learning from failure (ELF). Resilience (RES) Entrepreneurial Self-Efficacy (ESE) Emotion regulation (ER) internal locus of control (ILC) and Recovery capabilities (RC) are considered the most substantial antecedents. Individuals with higher RES, ESE, and ILC are more likely to learn deeper from failure. The significance of Emotion regulation and recovery ability was found significant. Recovery capabilities and emotion regulation enhance our understanding of cognitive and emotional processes that support effective learning in demanding entrepreneurial contexts. The findings have implications for entrepreneurs, policymakers and educators. The entrepreneurial training programs may benefit by embedding resilience, self-efficacy, emotion regulation, and recovery-capability-strengthening factors in their curriculum. Learning from one's failures to increase the probability of success requires educational institutions and support organizations to fortify these among entrepreneurs. This study presents a comprehensive analysis of psychological and cognitive factors in entrepreneurial learning from failure. In this regard, a fresh understanding is given on how these factors interplay and contribute to favorable learning outcomes.